Integrated Management of Borobudur World Heritage Site: A Conflict Resolution Effort - Susilo, Y Sri; Suroso, Amiluhur (Department of Management, Faculty of Economics and Business, Brawijaya University, 2014)
Management of The Borobudur Cultural Landsape, currently, only focus on the Borobudur Temple Compounds, while its hinterland including the surrounding communities are ignored. The management model is fragmented under three ministries, making it difficult for the coordination and synchronization. Management model like this is regarded as inefficient, ineffective, inharmonious and unfair, giving rise to the conflict. Thus, the purpose of this study is to examine the management model of The Borobudur World Heritage Site appropriate to eliminate conflicts and resolve the problems of benefit redistribution among stakeholders. Data collecting in this study is done by observation and survey, followed by braistorming, expert meetings and focus group discussions. The research results showed that the management of the Borobudur World Heritage Site needs to be done in a single management, unified, integrated, holistic, multi-stakeholders (central and local government, business and local communities) by way of a shared-responsibility. The governing body of the Borobudur World Heritage Site, according to the contitution, it should be the government organ that is autonomous or semi-autonomous and its primary purpose is preservation.Â Based on various inputs and considerations as well as the prevalence in the management of cultural heritage around the world, then the governing body of the Borobudur World Heritage Site are: (1) work unit with the Financial Application Pattern (FAP) of Public Service Agency (PSA) has a priority status; (2) a regular working unit, status avoided wherever possible; and (3) the State company (in the form of a limited liability company) status is not recommended.